Characteristics of the stretch-shortening cycle movement ability of male field hockey players - Kariyama, Y.; Akutsu, S.; Mizawa, T.; Teramoto, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The aim of this study was to investigate the characteristics of the stretch-shortening cycle (SSC) movement ability of male field hockey players by using various jump tests. Thirty-seven male field hockey players of the national top-level university team performed three jump tests (countermovement jump [CMJ], rebound jump [RJ], and drop jump [DJ]). The coach of the participant team in this study subjectively evaluated the players` footwork (sprint running and change of direction movements) ability during field hockey games. The results of all the analyses were as follows: 1) The top-level field hockey players had higher RJ and DJ abilities than the lower-level field hockey players. 2) A significant relationship was observed between the subjective evaluation points and the performances in the various jump (CMJ, RJ, and DJ) tests. These results indicate that CMJ, especially RJ and DJ are important SSC abilities for the performance of male field hockey players. Moreover, the CMJ, RJ, and DJ tests can be used for player selection and talent identification focused on footwork.